(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
This article systematically investigates the complex structure of human memory and its psychological aspects. The article analyzes the main types of memory — sensory memory, short-term memory, long-term memory — and their functional differences, physiological foundations, and psychological mechanisms. The psychological characteristics of memory — encoding, storage, retrieval processes — and factors influencing them, such as attention, emotional state, repetition, as well as the neurophysiological causes of forgetting, are comprehensively covered in the article.